The Mad Mrs. Rochester Revisited: The Involuntary Confinement of the Mentally Ill In South Africa - Haysom, Nicholas; Strous, Martin; Vogelman, Lloyd (PINS-Psychology in Society, 2026)
The involuntary confinement of the mentally ill describes the legal process by which a person is imprisoned for an indeterminate period not because they have committed any criminal act but because they are allegedly ill. The consequences of such imprisonment may be extreme on the person so detained. They lose not only the capacities and liberties of a free citizen but may also lose the right to refuse "medical" treatment including electro convulsive therapy.2 The mere committal to a psychiatric institution is stigmatising and potentially degrading. Although the allegedly ill person opposes or denies the need for incarceration and treatment, the initial decision ordering their committal takes place without their knowledge and is subsequently confirmed in their absence. The committal process, we argue, despite a legal veneer, is essentially an administrative procedure relying on the diagnosis and opinion of medical practitioners. The consequences of a faulty diagnosis are severe, and there is much evidence to suggest that psychiatry has not reached a stage where faulty diagnosis is unlikely.